Biology of tissue factor pathway inhibitor - Wood, J.; Ellery, Paul; Maroney, S.; Mast, A. (American Society of Hematology, 2014)
Recent studies of the anticoagulant activities of the tissue factor (TF) pathway inhibitor (TFPI) isoforms, TFPIa and TFPIß, have provided new insight into the biochemical and physiological meagulant activities. An alternative splicing event in the 59 untranslated region allows for translational regulation of TFPIß expression. TFPIa has 3 Kunitz-type inhibitor domains (K1, K2, K3) and a basic C terminus, whereas TFPIß has the K1 and K2 domains attached to a glycosylphosphatidyl inositol-anchored C terminus. TFPIa is the only isoform present in platelets, whereas endothelial cells produce both isoforms, secreting TFPIa and expressing TFPIb on the cell surface. TFPIa and TFPIß inhibit both TF-factor VIIa-dependent factor Xa (FXa) generation and free FXa. ProteinSenhances FXa inhibition by TFPIa. TFPIa produces isoform-specific inhibition of prothrombinase during the initiation of coagulation, an anticoagulant activity that requires an exosite interaction between its basic C terminus and an acidic region in the factor Va B domain. Platelet TFPIa may be optimally localized to dampen initial thrombin generation. Similarly, endothelial TFPIß may be optimally localized to inhibit processes that occur when endothelial TF is present, such as during the inflammatory response. © 2014 by The American Society of Hematology.